2010
DOI: 10.1007/s00535-010-0277-6
|View full text |Cite
|
Sign up to set email alerts
|

Accurate and simple method for quantification of hepatic fat content using magnetic resonance imaging: a prospective study in biopsy-proven nonalcoholic fatty liver disease

Abstract: This MRI method is simple and noninvasive, has excellent ability to quantify hepatic fat content even in NAFLD patients with mild steatosis or advanced fibrosis, and can be performed easily without special devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 35 publications
1
24
1
Order By: Relevance
“…In these two previous studies [6,19] and our own, the existence of hepatic steatosis was judged by the findings on unenhanced CT imaging. CT is a useful modality if steatosis is found in more than 30% of hepatocytes, but its ability to detect steatosis is reduced when lipid accumulation occurs in less than 30% of hepatocytes [20,21]. Thus, there is a possibility of underestimating de novo NAFLD after PD if the steatosis is mild; accordingly, its actual prevalence might be higher than reported in the above two studies and the present one.…”
Section: Discussioncontrasting
confidence: 78%
“…In these two previous studies [6,19] and our own, the existence of hepatic steatosis was judged by the findings on unenhanced CT imaging. CT is a useful modality if steatosis is found in more than 30% of hepatocytes, but its ability to detect steatosis is reduced when lipid accumulation occurs in less than 30% of hepatocytes [20,21]. Thus, there is a possibility of underestimating de novo NAFLD after PD if the steatosis is mild; accordingly, its actual prevalence might be higher than reported in the above two studies and the present one.…”
Section: Discussioncontrasting
confidence: 78%
“…This gold standard has been questioned by El-Badry et al [15] who showed that assessment of steatosis is strongly observer-dependent, not reproducible, and does not correlate well with DQS, as confirmed by other groups [29]. DQS showed good correlation with 1 H MRS in patients with NAFLD [30]. In the present study, histopathological assessment showed higher levels of steatosis but lower reliability when compared to 1 H MRS or DQS (Fig.…”
Section: Discussionsupporting
confidence: 73%
“…Patients were considered to have dyslipidemia if their fasting serum levels of cholesterol or triglycerides were equal to or higher than 220 or 150 mg/dL, respectively, or if they were taking lipid-lowering drugs [27,28]. Patients were considered to be diabetic if they had a fasting glucose level equal to or higher than 126 mg/dL, or if they were taking insulin or oral hypoglycemic agents [27][28][29][30][31][32][33]. Hyperuricemia was defined as a uric acid concentration of C7.0 mg/dL, based on guidelines released by the Japan Society of Gout and Nucleic Acid Metabolism, or if they were taking anti-hypreruricemia drugs.…”
Section: Data Collectionmentioning
confidence: 99%